Design and Build an Internet of Things (IoT) Automatic TV Broadcasting Antenna System - Jon Endri; Elizah Fitri; Suroso (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Nowadays, television is used for educational purposes. It is easily accessible through air-to-air broadcasts and can be connected via satellite. What is witnessed on a television screen is all image and sound elements. Many people feel uncomfortable watching television shows because when the television is used, the broadcasts that appear are not all images and sounds that can be seen and heard properly. Most antennas used by every household are patented in a certain position. Based on the existing description, the problem that would be solved is how to design an IoT-based TV broadcasting antenna system to make it easier to watch television with clear broadcasts and good sound without changing the antenna's position manually. With the design method, the tool to be made consists of a flowchart and a circuit design, namely, building a system with inputs, processes, and outputs. The automatic TV broadcasting antenna system based on the internet of things (IoT) is a system that points the antenna in the best position for each selected broadcast that can be controlled via Android using the Blynk IoT Application. After that, the test was carried out by taking data at two locations for the IoT antenna. The assessment results showed that each location was different, and the position of the antenna direction would also be different, so the location of the antenna must be changed by changing the angle contained in the Arduino IDE software.